Motion control strategy and stability analysis for high-speed cable-driven camera robots with cable inertia effects. (6th October 2016) - Wei, Huiling; Qiu, Yuanying; Su, Yu
The cable-based parallel camera robots possess characteristics of solitary way force, redundant actuation, and high-speed mobility. Therefore, research and solution on the stability are a challenging problem. In the available research literatures, there are limited studies to analyze the factors on the system stability for the high-speed cable-based parallel robots. However, when long-span cables and high maneuverability are involved, the effects of cable inertia on the dynamics should be carefully taken up. Thus, in this study, the effects of cable inertia on the stability of the high-speed cable-based parallel camera robots are studied. The dynamic model of the cable-based parallel robot is deduced with cable inertia based on the time-varying cable length dynamic model, the end-effector dynamic model, and the drive system dynamic model. Then, a tracking-control strategy for the camera robot is proposed based on a modified proportion-derivative (PD) forward controller in the end-effector position space. Further, the control strategy is demonstrated based on Lyapunov stability theory. Finally, numerical results show that camera robot is of stable-tracking performance. The control strategy is an effective approach to improve the stability of the camera robot.